2022
DOI: 10.1111/sapm.12488
|View full text |Cite
|
Sign up to set email alerts
|

Cauchy matrix approach to the SU(2) self‐dual Yang–Mills equation

Abstract: The Cauchy matrix approach is developed to solve the boldSUfalse(2false)$\mathbf {SU}(2)$ self‐dual Yang–Mills (SDYM) equation. Starting from a Sylvester matrix equation coupled with certain dispersion relations for an infinite number of coordinates, we derive some new relations that give rise to the SDYM equation under Yang's formulation. By imposing further constraints on complex independent variables, a broad class of explicit solutions of the equation under Yang's formulation are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In reductions of the BKP and CKP hierarchies, the reduced measures admit antisymmetry and symmetry property, respectively [24]. It is worth noting that the Sylvester equation was also developed to study some interesting higher-dimensional physical models, such as a Yajima-Oikawa system, a Mel'nikov model and a self-dual Yang-Mills equation (see [25][26][27]). In [27], based on the Sylvester Equation (3), Li et al investigated the master function S (i,j) = s T K j (I + M) −1 K i r and revealed that this function has the symmetric property S (i,j) T = −σ 2 S (j,i) σ 2 , where σ 2 is a Pauli matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In reductions of the BKP and CKP hierarchies, the reduced measures admit antisymmetry and symmetry property, respectively [24]. It is worth noting that the Sylvester equation was also developed to study some interesting higher-dimensional physical models, such as a Yajima-Oikawa system, a Mel'nikov model and a self-dual Yang-Mills equation (see [25][26][27]). In [27], based on the Sylvester Equation (3), Li et al investigated the master function S (i,j) = s T K j (I + M) −1 K i r and revealed that this function has the symmetric property S (i,j) T = −σ 2 S (j,i) σ 2 , where σ 2 is a Pauli matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the original Yang-Mills equation [17] is not integrable in general but the self-dual gauge field equations are integrable, e.g., in the sense of Painlevé property [5,12]. One can also refer to an early review [10] or a recent paper [6] and the references therein, or a recent theses [4], for more details.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent paper [6] we developed an approach to construct solutions to the SU(2) SDYM equation by means of the Cauchy matrix method. It is based on a framework of the Cauchy matrix approach to the Ablowitz-Kaup-Newell-Segur (AKNS) equations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations